The Baader-Schelling controversy in Schelling’s Das System der Weltalter: Elohim as divine proxies - Gaisin, Aleksandr (International journal of philosophy and theology, 2023)
This paper examines the controversy between Franz von Baader and Schelling as it takes place in Schelling’s lecture course Das System der Weltalter. This particular instance of their disagreement involves Schelling criticising Baader for his notion of the biblical Elohim as divine proxies. The paper first provides a background to Baader-Schelling philosophical feud before examining Schelling’s remarks against Baader in the System der Weltalter. Then, Baader’s writings on Elohim are looked into in the light of their connection to Baader’s conception of creation as falling-away and Baader’s source for interpreting Elohim as proxies, including Saint Martin and Kabbalah. Thereafter, Schelling’s criticism of Baader is analysed and interpreted in the context of the System der Weltalter. The paper aims to achieve several things: to show the presence of distorted kabbalistic influence in Baader and its discussion in Schelling; to revise Koslowski’s view on Baader’s creation narrative by pointing out how Baader’s Elohim/divine proxies function to form a rather dualistic relation between God and creation; and to interpret Schelling’s convoluted and difficult reply to Baader displaying that at stake between the two thinkers were questions of God’s ineffability and freedom as well as God’s involvement into creation.